Context-Specific Dynamics of Centrally Planned Macro Program for School Infrastructure Reform - Chongbang, Karna Bahadur; Siwakoti, Rabindra (Molung Educational Frontier, 2024)
The educational program evolved at the national level manifests in a general macro program. The school infrastructure development program through the President’s Education Reform Program (PERP) is one of the centrally developed educational programs in Nepal, as the case of this research article. The objective of this article is to analyze the context dynamics of centrally evolved school infrastructure (ICT and classroom building) program installation. The primary data employed in this article were drawn from the stakeholders of three program school cases situated in Sarlahi and Rautahat districts belonging to an embedded multiple-case study design of qualitative research methodology. FGD, key informant (KI) interviews, and general observation methods were used for information elicitation. The research findings reveal that centrally developed macro program policy interacts with school system-specific micro-contexts or central policy contexts which make program policy be implemented irrespective of the prioritized need, adapted with a modified technical design responding to the school-specific resources, and practiced with diverse school leadership styles. In the lapses of coordination and commitment of the tiered governance systems, the PERP or any other macro-program policy becomes strange for the implementers. The complex interaction of school-specific systems dynamics consisting of school infrastructural needs, stakeholder involvement, established school leadership styles, and initiation of local government authority make central macro policy be enacted and adapted rather than be linearly implemented. This implies incorporating the school-specific dynamics as a core component of the education plan for the formation of pragmatic program policy to enact effectively.